2019
DOI: 10.1109/tsg.2018.2834219
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Building Energy Optimization Using Deep Reinforcement Learning

Abstract: Unprecedented high volumes of data are becoming available with the growth of the advanced metering infrastructure. These are expected to benefit planning and operation of the future power system, and to help the customers transition from a passive to an active role. In this paper, we explore for the first time in the smart grid context the benefits of using Deep Reinforcement Learning, a hybrid type of methods that combines Reinforcement Learning with Deep Learning, to perform on-line optimization of schedules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
233
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(235 citation statements)
references
References 29 publications
1
233
0
1
Order By: Relevance
“…An energy optimization problem in a smart grid is formulated in [100]. An on-line energy scheduling strategy is learned using deep Q-learning and deep policy gradient methods.…”
Section: Aiot Perception Layer -Smart Gridmentioning
confidence: 99%
“…An energy optimization problem in a smart grid is formulated in [100]. An on-line energy scheduling strategy is learned using deep Q-learning and deep policy gradient methods.…”
Section: Aiot Perception Layer -Smart Gridmentioning
confidence: 99%
“…Here, λ F t,n is the diesel generator fuel price in $/L adopted from [32]. The fuel consumption F i,t,n of diesel generator can be expressed as a quadratic polynomial function (17), with coefficients a f = 0.0001773 L/kW 2 , b f = 0.1709 L/kW , and c f = 14.67L adopted from [33]. Constraints (18) .…”
Section: Appendix Mg Optimal Power Management Formulationmentioning
confidence: 99%
“…The general problem with majority of the algorithms is that, for optimization they compute partial or the entire solution space to choose the best one, and hence are time consuming. [5] explores an interesting approach that avoids computing the entire search space using Deep Reinforcement Learning (DRL) to optimize schedules for building's energy management systems. The authors investigate two DRL based algorithms, Deep Policy Gradient (DPG) and Deep Q-Learning (DQN) for building a on-line large scale solution and conclude it to be more effective than traditional solutions.…”
Section: Related Workmentioning
confidence: 99%
“…We model this community as a multi-agent environment where each agent represents a building. Previous works [5] have demonstrated that deep reinforcement learning (DRL) is an effective technique for energy management in a single building management system. Considering this, we propose a DRL-based solution to optimize energy sharing between multiple such buildings.…”
Section: Introductionmentioning
confidence: 99%